2022
DOI: 10.1155/2022/7523673
|View full text |Cite|
|
Sign up to set email alerts
|

Impacts of Low-Dose Total Glycosides of Tripterygium wilfordii plus Methotrexate on Immunological Function and Inflammation Level in Patients with Rheumatoid Arthritis

Abstract: Purpose. This research mainly clarifies the impacts of low-dose- (LD-) total glycosides of Tripterygium wilfordii (GTW) plus methotrexate (MTX) on immunological function and inflammation level in patients with rheumatoid arthritis (RA). Methods. We enrolled 106 RA patients treated in Yanbian University Hospital between July 2019 and July 2021, including 56 cases (research group) intervened by LD-total GTW plus MTX and 50 cases (control group) treated with MTX, in addition to conventional treatment given to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%